High-thermal-conductivity well cementation admixture, application thereof and well cementation cement slurry
A high thermal conductivity cementing admixture with specific particle sizes and surfactant improves cement slurry fluidity and stability, enhancing thermal conductivity and compressive resistance in geothermal wells.
Patent Information
- Application Number
- CN202310697212.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-13
Smart Images

Figure CN119118559A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of well cementing, and in particular to a high thermal conductivity well cementing admixture and application thereof and well cementing cement slurry. Background Art
[0002] At present, geothermal development mainly adopts the development mode of "taking water for heat" which is to extract groundwater, exchange heat and then reinject it. However, this mode is restricted by many factors such as incomplete reinjection and environmental pollution. Under such a background, the underground high-efficiency "taking heat without taking water" technology gradually replaces the "taking water for heat" technology and becomes the current mainstream development trend.
[0003] The technology of extracting heat without taking water mainly includes two implementation modes: single well coaxial casing downhole heat extraction technology and U-shaped connecting well heat extraction technology. In the more mature U-shaped connecting well technology, the cement ring acts as a heat conductor. Among them, the cement ring is composed of cement stone formed after the cementing cement slurry is solidified. The cement stone needs to have good thermal conductivity and compressive resistance.
[0004] Adding thermal conductive fillers such as graphite, alumina, magnesium oxide, zinc oxide, aluminum nitride, boron nitride, silicon carbide, aluminum alloy, copper powder, aluminum powder, molybdenum powder, tungsten powder, zinc powder, iron powder, nickel powder, etc. to cementing slurry can improve the thermal conductivity of cement paste to a certain extent. However, the addition of thermal conductive fillers will make the compatibility of various interfaces in the cement paste worse, which is not conducive to the fluidity and sedimentation stability of the slurry, and is prone to stratification, segregation, hardening, heating, etc., and may even reduce the compressive strength of the cement paste.
[0005] CN110002798A discloses a leakproof cement slurry for cementing. The leakproof cement slurry comprises the following components: water, oil well cement, bridging particles, quartz sand, microsilica powder, and cement admixture. The leakproof cement slurry is made by reasonable gradation of granular materials of different particle sizes, so that the cement stone formed after the leakproof cement slurry is thickened has high compressive strength and high interface bonding strength, and can achieve effective isolation of oil and water layers. Although the close stacking between particles can reduce the interface thermal resistance, the cement hydration product alone cannot provide sufficient thermal conductivity.
[0006] Therefore, it is urgent to provide a high thermal conductivity cementing admixture and cementing cement slurry that can ensure the fluidity and stability of the slurry so that the solidified cement stone can have both good thermal conductivity and compressive resistance. Summary of the invention
[0007] The purpose of the present invention is to solve the problems in the prior art that the cement slurry has poor fluidity and sedimentation stability, and the cement stone formed after hydration is difficult to have both high thermal conductivity and high compressive resistance, and to provide a high thermal conductivity cementing admixture and its application and cementing cement slurry.
[0008] In order to achieve the above object, the first aspect of the present invention provides a high thermal conductivity cementing admixture, wherein the cementing admixture comprises: 100 parts by weight of a coarse particle size component, 40-120 parts by weight of a fine particle size component, 0.05-0.85 parts by weight of a nano component, and 0.1-3.5 parts by weight of a surfactant;
[0009] Wherein, the particle size of the coarse particle size component is 100-1000 μm, the particle size of the fine particle size component is 1-80 μm, and the particle size of the nano particle component is 1-50 nm;
[0010] Among them, the coarse particle size component is selected from one or more of quartz sand, zinc oxide, and aluminum oxide; the fine particle size component is selected from one or more of aluminum nitride, boron nitride, silicon carbide, graphite, copper powder, and iron powder; the nano component is selected from one or more of nano silver particles, nano copper particles, carbon nano tubes, and graphene; the surfactant is selected from one or more of sodium dodecylbenzene sulfonate, polyvinyl pyrrolidone, and hexadecyltrimethylammonium bromide.
[0011] The second aspect of the present invention provides a use of the high thermal conductivity cementing admixture described in the first aspect of the present invention in cementing cement slurry.
[0012] The third aspect of the present invention provides a cementing cement slurry, wherein the raw materials for preparing the cement slurry include: 100 parts by weight of oil well cement, 25-65 parts by weight of the high thermal conductivity cementing admixture described in any one of claims 1-7, 2.5-5 parts by weight of a fluid loss reducer, 1.5-4.5 parts by weight of an early strength agent, 0.25-1 parts by weight of a dispersant, 0.005-0.5 parts by weight of a defoaming agent and 50-90 parts by weight of water.
[0013] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:
[0014] 1) The high thermal conductivity cementing admixture provided in the present invention introduces a nano-component with a particle size of nanometers, and is graded with a coarse particle size component and a fine particle size component, so as to improve the thermal conductivity of cement paste while ensuring the mechanical strength of cement paste;
[0015] 2) The high thermal conductivity cementing admixture provided in the present invention has a wide range of raw material sources and a simple preparation method. It can be used in the cementing technology of U-shaped connected wells in geothermal wells. It can effectively improve the thermal conductivity of the cement sheath while ensuring the compressive strength of the cement sheath, thereby giving full play to the advantages of the long heating section of the technology and improving the heat extraction efficiency of geothermal wells.
[0016] 3) The cement slurry provided in the present invention has good slurry fluidity and high stability. The cement stone formed by curing at 90°C and 10Mpa for 24 hours has a high degree of hydration, good thermal conductivity and qualified compressive strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a SEM image of the cement paste in Example 1 observed using a JSM-7200F scanning electron microscope at a magnification of 1000;
[0018] Figure 2 is a SEM image of the cement stone in Comparative Example 1 observed using a JSM-7200F scanning electron microscope at a magnification of 1000;
[0019] Figure 3 is a SEM image of the cement stone in Comparative Example 3 observed with a JSM-7200F scanning electron microscope at a magnification of 1000;
[0020] Figure 4 is a SEM image of the cement stone in Comparative Example 1 observed using a JSM-6510A scanning electron microscope at a magnification of 600;
[0021] Figure 5 is a SEM image of the cement stone in Comparative Example 1 observed using a JSM-6510A scanning electron microscope at a magnification of 200;
[0022] Figure 6 is a SEM image of the cement paste in Example 1 observed using a JSM-6510A scanning electron microscope at a magnification of 200;
[0023] Figure 7 is a SEM image of the cement paste in Example 1 observed using a JSM-6510A scanning electron microscope at a magnification of 600;
[0024] Figure 8 This is a hydration dynamics test diagram of the cement slurry in Comparative Example 1;
[0025] Fig. 9 This is a hydration dynamics test diagram of the cement slurry in Example 1. DETAILED DESCRIPTION
[0026] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0027] The first aspect of the present invention provides a high thermal conductivity cementing admixture, wherein the cementing admixture comprises: 100 parts by weight of a coarse particle size component, 40-120 parts by weight of a fine particle size component, 0.05-0.85 parts by weight of a nano component, and 0.1-3.5 parts by weight of a surfactant;
[0028] Wherein, the particle size of the coarse particle size component is 100-1000 μm, the particle size of the fine particle size component is 1-80 μm, and the particle size of the nano particle component is 1-50 nm;
[0029] Among them, the coarse particle size component is selected from one or more of quartz sand, zinc oxide, and aluminum oxide; the fine particle size component is selected from one or more of aluminum nitride, boron nitride, silicon carbide, graphite, copper powder, and iron powder; the nano component is selected from one or more of nano silver particles, nano copper particles, carbon nano tubes, and graphene; the surfactant is selected from one or more of sodium dodecylbenzene sulfonate, polyvinyl pyrrolidone, and hexadecyltrimethylammonium bromide.
[0030] Among them, in the present invention, the component forms of the nano-component include particles (nano-silver particles and nano-copper particles), linear bodies (carbon nanotubes) and flake bodies (graphene). When the nano-component is a linear body, the particle size refers to the outer diameter of the linear body, and when the nano-component is a flake body, the particle size refers to the thickness of the flake body.
[0031] Among them, in the present invention, by selecting specific components and regulating the particle sizes of coarse-grained components, fine-grained components and nano-components, and adding a small amount of surfactant, the compatibility of high thermal conductivity cementing admixtures with cement can be significantly improved, so that the cement stone formed by the cementing cement slurry containing thermal conductive cementing admixtures after hydration can have both good thermal conductivity and compressive resistance.
[0032] In a preferred embodiment of the present invention, the cementing admixture comprises: 100 parts by weight of a coarse particle size component, 60-100 parts by weight of a fine particle size component, 0.1-0.5 parts by weight of a nano component, and 0.5-2.5 parts by weight of a surfactant.
[0033] In a further preferred embodiment of the present invention, the cementing admixture comprises: 100 parts by weight of a coarse particle size component, 75-85 parts by weight of a fine particle size component, 0.2-0.3 parts by weight of a nano component, and 1-1.5 parts by weight of a surfactant.
[0034] In one embodiment of the present invention, the particle size of the coarse particle size component can be 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 900, 950, 1000 μm, and any value in the range formed by any two of these point values.
[0035] In one embodiment of the present invention, the particle size of the fine particle size component can be 1, 2, 3, 4, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80 μm, and any value in the range formed by any two of these point values.
[0036] In one embodiment of the present invention, the particle size of the nano-component can be 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50 nm, and any value in the range formed by any two of these point values.
[0037] Among them, in the present invention, taking the coarse particle size component as an example, the particle sizes of the coarse particle size component, the fine particle size component and the nanometer component are explained. When the coarse particle size component includes more than two components, the particle sizes of the components can be the same or different, as long as they are within the limited range of the particle size of the coarse particle size component. The inventor has found through research that when the particle sizes of the coarse particle size component, the fine particle size component and the nanometer component are within the above-defined range, the cementing admixture has a better modification effect on the flowability and sedimentation performance of the cement slurry and the compressive resistance and thermal conductivity of the cement stone.
[0038] In one embodiment of the present invention, the purity of the quartz sand, zinc oxide and aluminum oxide is ≥ 98% each, preferably 98-99.9%.
[0039] In one embodiment of the present invention, the aluminum oxide is selected from one or more of α-aluminum oxide, γ-aluminum oxide, and θ-aluminum oxide, preferably α-aluminum oxide.
[0040] In one embodiment of the present invention, the purity of the aluminum nitride, boron nitride, silicon carbide, graphite, copper powder, and iron powder is independently ≥ 98%, preferably 98-99.9%.
[0041] In one embodiment of the present invention, the silicon carbide is selected from α-silicon carbide and / or β-silicon carbide, preferably α-silicon carbide. The graphite is selected from flake graphite and / or spherical graphite, preferably flake graphite, and more preferably natural flake graphite.
[0042] In one embodiment of the present invention, the purity of the nano-silver particles, nano-copper particles, carbon nanotubes and graphene is ≥ 98%, preferably 98-99.9%.
[0043] In one embodiment of the present invention, the carbon nanotubes have an inner diameter ID of 3-12 nm, preferably 5-10 nm; an outer diameter OD of 8-50 nm, preferably 20-30 nm; and a length of 1-50 μm, preferably 10-20 μm.
[0044] In one embodiment of the present invention, the graphene is multilayer graphene, wherein the number of layers of the multilayer graphene is ≤50, preferably 1-30.
[0045] In one embodiment of the present invention, the coarse particle size component is selected from any two of quartz sand, zinc oxide, and aluminum oxide, preferably zinc oxide and aluminum oxide, wherein the mass ratio of zinc oxide to aluminum oxide is 1:1-10, preferably 1:3-5.
[0046] In one embodiment of the present invention, the fine particle size component is selected from at least two of aluminum nitride, boron nitride, silicon carbide, graphite, copper powder, and iron powder, preferably at least three or four of aluminum nitride, boron nitride, silicon carbide, graphite, copper powder, and iron powder, and more preferably boron nitride, silicon carbide, graphite, and copper powder. The mass ratio of boron nitride, silicon carbide, graphite, and copper powder is 1:0.5-1.5:0.2-0.6:1-2.
[0047] The second aspect of the present invention provides a use of the high thermal conductivity cementing admixture described in the first aspect of the present invention in cementing cement slurry.
[0048] The third aspect of the present invention provides a geothermal well cementing cement slurry, wherein the raw materials for preparing the cement slurry include: 100 parts by weight of oil well cement, 25-65 parts by weight, preferably 35-50 parts by weight of the high thermal conductivity cementing admixture described in the first aspect of the present invention, 2.5-5 parts by weight, preferably 3.5-4.5 parts by weight of a fluid loss reducer, 1.5-4.5 parts by weight, preferably 2.5-3.5 parts by weight of an early strength agent, 0.25-1 parts by weight, preferably 0.5-0.75 parts by weight of a dispersant, 0.005-0.5 parts by weight, preferably 0.1-0.15 parts by weight of a defoamer and 50-90 parts by weight, preferably 65-75 parts by weight of water.
[0049] In one embodiment of the present invention, the oil well cement is selected from Grade G high sulfate resistance oil well cement.
[0050] In one embodiment of the present invention, the fluid loss agent is selected from one or more of DZJ-Y fluid loss agent, CMC (carboxymethyl cellulose), PVA (polyvinyl alcohol), and HEC (hydroxyethyl cellulose).
[0051] In one embodiment of the present invention, the early strength agent is selected from sulfate early strength agents, preferably, the sulfate early strength agent is selected from one or more of sodium sulfate, calcium sulfate and potassium sulfate.
[0052] In one embodiment of the present invention, the dispersant is selected from polycarboxylic acid dispersants. The present invention does not specifically limit the polycarboxylic acid dispersants, and conventional polycarboxylic acid dispersants in the art can be used in the present invention.
[0053] In one embodiment of the present invention, the defoamer is selected from one or more of polyether defoamers (polypropylene glycol, ethylene oxide, glycerol), silicone defoamers (polydimethylsiloxane and / or ethylene glycol siloxane), and alcohol defoamers (diethylhexanol and / or isoamyl alcohol).
[0054] In one embodiment of the present invention, the method for preparing the cement slurry comprises: uniformly mixing the oil well cement, high thermal conductivity cementing admixture, fluid loss reducer, early strength agent, dispersant and defoamer to obtain the cement slurry.
[0055] In one embodiment of the present invention, the method for preparing the cement slurry preferably comprises the following steps:
[0056] (1) dispersing the nano components and surfactant in the high thermal conductivity cementing admixture in water to prepare a nano dispersion;
[0057] (2) mixing the coarse particle size component and the fine particle size component in the high thermal conductivity cementing admixture uniformly to obtain a mixed powder;
[0058] (3) mixing the oil well cement, the early strength agent and the mixed powder uniformly to obtain the oil well cement mixed powder;
[0059] (4) First, a fluid loss reducer and a dispersant are added into water, and then the nano-dispersion liquid, the oil well cement mixed powder and the defoamer are added in sequence, and mixed evenly to obtain the cement slurry.
[0060] The present invention does not specifically limit the dispersion, mixing and blending, and can be performed according to methods known in the art. By controlling the order of adding the components, the dispersion of the coarse particle size component, the fine particle size component and the nanometer component in the cement slurry can be further improved, thereby further improving the thermal conductivity and compressive resistance of the cement sheath.
[0061] The present invention will be described in detail below through examples.
[0062] Polyvinyl pyrrolidone was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., product number P110607-25g, and the defoaming agent was diethyl hexanol.
[0063] Example 1
[0064] (1) Add 3.0 g of polyvinyl pyrrolidone to a 400 ml beaker, add 300 g of deionized water under stirring, and then add 0.4 g of nano-component multilayer graphene (particle size of 10 nm, purity of 99.9%, number of layers of 30), and perform ultrasonic treatment for 360 s, wherein the ultrasonic power is 300 W, to obtain a nano-dispersion liquid;
[0065] (2) 160 g of α-alumina (particle size of 200 μm, purity of 99%), 40 g of zinc oxide (particle size of 800 μm, purity of 99%), 16 g of natural flake graphite (thickness of 45 μm, purity of 99.9%), 40 g of α-silicon carbide (particle size of 45 μm, purity of 99%), 40 g of boron nitride (particle size of 2 μm, purity of 99%) and 64 g of copper powder (particle size of 45 μm, purity of 99.9%) were mixed and uniformly mixed to obtain a mixed powder;
[0066] (3) 800 g of G-grade high sulfate-resistant oil well cement, 24 g of anhydrous sodium sulfate as an early strength agent and the above mixed powder were mixed and stirred to obtain an oil well cement mixed powder;
[0067] (4) 32 g of DZJ-Y fluid loss additive and 4 g of polycarboxylic acid dispersant were added to 250 g of water, and an OWC-9040A constant speed agitator was turned on to stir at a speed of 1000 r / min. The above-mentioned nano-dispersion liquid was added while stirring. After the nano-dispersion liquid was added, the speed was increased to 4000 r / min, and the above-mentioned oil well cement mixed powder was added within 15 s, and 1.0 g of defoaming agent was added. Then, the speed was adjusted to 12000 r / min and stirred for 35 s to obtain cement slurry.
[0068] Example 2
[0069] (1) Add 1 g of hexadecyltrimethylammonium bromide to a 400 ml beaker, add 300 g of deionized water under stirring, and then add 0.2 g of nano-component carbon nanotubes (ID is 10 nm, OD is 25 nm, and length is 10 μm), and perform ultrasonic treatment for 360 s, wherein the ultrasonic power is 300 W, to obtain a nano-dispersion liquid;
[0070] (2) 160 g of quartz sand (particle size 400 μm, purity 99%), 40 g of zinc oxide (particle size 800 μm, purity 99%), 10 g of natural flake graphite (thickness 45 μm, purity 99.9%), 30 g of α-silicon carbide (particle size 45 μm, purity 99%), 60 g of boron nitride (particle size 2 μm, purity 99%) and 30 g of copper powder (particle size 45 μm, purity 99.9%) were mixed and uniformly mixed to obtain a mixed powder;
[0071] (3) 800 g of G-grade high sulfate-resistant oil well cement, 24 g of anhydrous sodium sulfate as an early strength agent and the above mixed powder were mixed and stirred to obtain an oil well cement mixed powder;
[0072] (4) 32 g of DZJ-Y fluid loss additive and 4 g of polycarboxylic acid dispersant were added to 150 g of water, and an OWC-9040A constant speed agitator was turned on to stir at a speed of 1000 r / min. The above-mentioned nano-dispersion liquid was added while stirring. After the nano-dispersion liquid was added, the speed was increased to 4000 r / min, and the above-mentioned oil well cement mixed powder was added within 15 seconds, and 1.0 g of defoaming agent was added. Then, the speed was adjusted to 12000 r / min and stirred for 35 seconds to obtain cement slurry.
[0073] Example 3
[0074] (1) Add 5 g of sodium dodecylbenzene sulfonate to a 400 ml beaker, add 300 g of deionized water under stirring, and then add 0.8 g of nano copper particles (particle size 50 nm, purity 99.8%), first ultrasonically treat for 15 min, wherein the ultrasonic power is 300 W, and then magnetically stir for 5 min to obtain a nano dispersion;
[0075] (2) 160 g of α-alumina (particle size of 200 μm, purity of 99%), 40 g of zinc oxide (particle size of 800 μm, purity of 99%), 30 g of natural flake graphite (thickness of 45 μm, purity of 99.9%), 40 g of β-silicon carbide (particle size of 45 μm, purity of 99%), 80 g of boron nitride (particle size of 2 μm, purity of 99%) and 50 g of copper powder (particle size of 45 μm, purity of 99.9%) were mixed and uniformly mixed to obtain a mixed powder;
[0076] (3) 800 g of G-grade high sulfate-resistant oil well cement, 24 g of anhydrous sodium sulfate as an early strength agent and the above mixed powder were mixed and stirred to obtain an oil well cement mixed powder;
[0077] (4) 32 g of DZJ-Y fluid loss additive and 4 g of polycarboxylic acid dispersant were added to 180 g of water, and an OWC-9040A constant speed agitator was turned on to stir at a speed of 1000 r / min. The above-mentioned nano-dispersion liquid was added while stirring. After the nano-dispersion liquid was added, the speed was increased to 4000 r / min, and the above-mentioned oil well cement mixed powder was added within 15 s, and 1.0 g of defoaming agent was added. Then, the speed was adjusted to 12000 r / min and stirred for 35 s to obtain cement slurry.
[0078] Example 4
[0079] The same as Example 3, the difference is that: in step (2), zinc oxide, α-silicon carbide and boron nitride are omitted, the amount of α-alumina used is 200g, the amount of natural flaky graphite used is 60g, and the amount of copper powder used is 140g.
[0080] Example 5
[0081] The same as Example 3, the difference is that in step (2), natural flaky graphite is omitted and the amount of copper powder used is 80g.
[0082] Example 6
[0083] The same as Example 3, except that: in step (1), the natural flaky graphite with a thickness of 45 μm is replaced by an equal amount of natural flaky graphite with a thickness of 15 μm.
[0084] Example 7
[0085] The same as Example 3, except that in step (1), the amount of polyvinyl pyrrolidone used is 1.2 g, and the ultrasonic treatment is performed for 1200 s.
[0086] Example 8
[0087] The same as Example 3, except that an equal amount of DZJ-Y fluid loss additive is replaced by CMC (carboxymethyl cellulose).
[0088] Comparative Example 1:
[0089] (1) 800 g of G-grade high sulfate-resistant oil well cement and 24 g of anhydrous sodium sulfate as an early strength agent were mixed to obtain an oil well cement mixed powder;
[0090] (2) 32 g of DZJ-Y fluid loss additive and 4 g of polycarboxylic acid dispersant were added to 320 g of water, and an OWC-9040A constant speed agitator was turned on. The mixture was stirred at a speed of 1000 r / min for 20 s, and then the speed was increased to 4000 r / min. The above-mentioned oil well cement mixed powder was added within 15 s, and 1.0 g of defoaming agent was added. Then the speed was adjusted to 12000 r / min and stirred for 35 s to obtain cement slurry.
[0091] Comparative Example 2:
[0092] The same as Example 4, except that in step (1), the nano-component nano-copper particles and ultrasonic treatment are omitted.
[0093] Comparative Example 3:
[0094] The same as Example 4, except that in step (2), the particle sizes of α-alumina and copper powder and the thickness of natural flaky graphite are all 200 μm.
[0095] Comparative Example 4:
[0096] The same as Example 4, except that in step (2), the copper powder is replaced by molybdenum powder of the same particle size in equal amounts.
[0097] Test Example 1
[0098] The cement slurries prepared in Examples 1-8 and Comparative Examples 1-4 were poured into test molds of 50 mm × 50 mm × 50 mm, sealed, and placed in a Chandler 7375 high temperature and high pressure curing box, set at 90°C and 10 MPa, and then demolded after curing for 24 hours to obtain cement stone samples. The thermal conductivity, compressive strength, fluidity index, consistency coefficient, and upper and lower density difference of the cement stone samples at 90°C were tested respectively, and the test results are shown in Table 1:
[0099] The cement stone samples were placed in an oven and dried at 60°C for 24 hours to remove moisture. The thermal conductivity of the cement stone at 90°C was tested using the Hotdisk2500S thermal conductivity meter according to the thermal conductivity and thermal diffusivity test standard ISO 22007-2-2015, using the transient plane heat source method. The compressive strength of the cement stone samples was then tested using the 4207D digital compressive strength tester according to the standard GB / T 19139-2012 oil well cement test method.
[0100] The fluidity index and consistency coefficient were tested using a six-speed rheometer model ZNN-D6. 350 mL of the prepared cement slurry was taken and put into a sample cup. The readings used to calculate the viscosity and fluidity index were recorded at speeds of 3 r / min, 6 r / min, 100 r / min, 200 r / min, 300 r / min, and 600 r / min, respectively. The fluidity index and consistency coefficient of the slurry were calculated using a power law model.
[0101] Testing method for upper and lower density difference: let the prepared cement slurry stand at room temperature for 15 minutes, take the top slurry and the bottom slurry respectively, pour them into the density meter for measurement, and record the difference.
[0102] Table 1
[0103]
[0104]
[0105] It can be seen from Table 1 that, compared with Comparative Example 1, the high thermal conductivity cementing admixture provided in the present invention, when used in cementing cement slurry, can ensure the thermal conductivity and compressive strength of the cement stone generated after the cementing cement slurry is cured, while the slurry has good fluidity and sedimentation stability.
[0106] By comparing Example 3 and Example 4, it can be seen that, under the premise that the addition amounts of the coarse particle size component and the fine particle size component remain unchanged, increasing the types of the coarse particle size component and the fine particle size component can significantly improve the slurry fluidity and sedimentation stability of the cement slurry.
[0107] By comparing Example 3 and Example 5, it can be seen that, under the premise of keeping the amount of fine particle size component added unchanged, adding natural flaky graphite can significantly improve the thermal conductivity of cement paste.
[0108] By comparing Example 3 and Example 6, it can be seen that by adjusting the particle size of natural flaky graphite in the fine particle size component, the sedimentation stability of cement slurry can be improved and the thermal conductivity of cement paste can be increased.
[0109] By comparing Example 3 and Example 7, it can be seen that by adjusting the amount of surfactant used, the thermal conductivity and compressive resistance of cement stone can be significantly improved.
[0110] By comparing Example 3 and Example 8, it can be seen that the selection of DZJ-Y fluid loss additive can significantly improve the sedimentation stability of cement slurry and the compressive properties of cement paste.
[0111] By comparing Example 4 with Comparative Examples 2 and 3, it can be seen that the three-level grading method of the coarse particle size component, the fine particle size component and the nano component can significantly improve the thermal conductivity and compressive resistance of the cement paste.
[0112] By comparing Example 4 and Comparative Example 4, it can be seen that by selecting specific components, the compatibility of the high thermal conductivity cementing admixture with cement can be significantly improved, so that the cement stone formed by the cementing cement slurry containing the thermal conductive cementing admixture after hydration can have both good thermal conductivity and compressive resistance.
[0113] Test Example 2
[0114] The crushed samples after the compressive strength test of Example 1, Comparative Example 1 and Comparative Example 3 were respectively taken and dried in an oven at 60°C to constant weight. A thin slice of about 5 mm × 5 mm × 1 mm was taken and subjected to gold spraying. Then, the thin slice was characterized using a JSM-7200F and a JSM-6510A scanning electron microscope (SEM). The characterization results are shown in FIG. Figure 1-7 shown.
[0115] in, Figure 1-3 The SEM images of cement paste in Example 1, Comparative Example 1 and Comparative Example 3 were observed using a JSM-7200F scanning electron microscope at a magnification of 1000. Figure 1 It can be seen that the surface of the cement stone in Example 1 is dense, basically free of voids, and the crusted calcium hydroxide crystals and natural flaky graphite crystals can be clearly seen, among which a large number of gel-like CSH crystals, which are mid-term hydration products, appear around the natural flaky graphite. This is because the hydrophobic effect between the natural flaky graphite and the nano-component causes the water molecules on its periphery to aggregate relatively, thereby promoting the hydration of C3S and C2S in the cement. At the same time, a more reasonable particle size distribution enables the nano-component to be filled into the micropores or gel pores in a certain orientation, thereby reducing the thermal resistance through the bridging effect.
[0116] Depend on Figure 2 It can be seen that the microstructure of cement paste without high thermal conductivity cementing admixture is loose, with a large number of pores larger than 10 μm, and the hydration degree is relatively low, and clinker particles such as C3S and C2S in the early stage of hydration can still be seen. Figure 3 It can be seen that when the particle sizes of the coarse-grained component and the fine-grained component are the same, the average pore size on the surface of the cement stone is slightly reduced, and the number is slightly reduced, but the degree of hydration is still not ideal. This is because the system without particle size grading has a relatively single pore filling, and the nano-components will be adsorbed on one side of the macropore in an irregular orientation and cannot play a key bridging role.
[0117] Figure 4-5 The SEM images of the cement stone in Comparative Example 1 observed by a JSM-6510A scanning electron microscope at magnifications of 1600 and 1200, respectively. Figure 6-7 The SEM images of the cement stone in Example 1 observed by a JSM-6510A scanning electron microscope at 600 magnifications and 200 magnifications respectively.
[0118] By comparison Figure 4-7 It can be seen that the cement stone in Comparative Example 1 is loose as a whole after curing, with a low degree of hydration, a large number of exposed pores, a large number of unhydrated clinker particles can be seen around the pores, and the surface flatness of the cement stone is poor. When the heat flow passes through the unhydrated particles and large pores, a large thermal resistance will be generated, limiting the thermal conductivity of the material. The cement stone in Example 1 is more compact as a whole after curing, and a relatively continuous thermal conduction path is formed on the surface of the cement stone, which can greatly improve the thermal conductivity of the cement stone.
[0119] Test Example 3
[0120] The hydration dynamics of the cement slurries in Comparative Example 1 and Example 1 were tested at 90°C and 10 MPa using a French Capac C80 mixed reaction microcalorimeter. The results are as follows: Figure 8-9 shown.
[0121] in, Figure 8 , the reaction heat is -179.324 (J / g), T: 88.90-88.89 (℃); t: 4.1-26.6 (hours); peak maximum: 88.908 (℃) / 8.279 (hours); peak height: 38.873 (mw); extrapolation starting point: 88.903 (℃) / 7.041 (hours); offset: 88.908 (℃) / 10.29 (hours); baseline type: straight line; mass used: 2550 mg (initial).
[0122] Fig. 9, the reaction heat is -185.736 (J / g), T: 88.87 to 88.88 (℃); t: 3.5 to 39.1 (hours); peak maximum: 88.891 (℃) / 7.243 (hours); peak height: 40.698 (mw); extrapolation starting point: 88.885 (℃) / 5.958 (hours); offset: 88.886 (℃) / 8.999 (hours); baseline type: straight line; mass used: 2550 mg (initial).
[0123] By comparison Figure 8 and Fig. 9 It can be seen that the hydration heat exothermic peak in Example 1 is advanced, the peak height increases, and the integrated reaction heat increases. Combined with the SEM image, it can be explained that the addition of high thermal conductivity cementing admixture can promote the hydration of cement slurry and thus improve the thermal conductivity and compressive resistance of cement paste.
[0124] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various specific technical features in any suitable manner. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations. However, these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A high thermal conductivity cementing admixture, characterized in that: The cementing admixture comprises: 100 parts by weight of a coarse particle size component, 40-120 parts by weight of a fine particle size component, 0.05-0.85 parts by weight of a nanometer component, and 0.1-3.5 parts by weight of a surfactant; Wherein, the particle size of the coarse particle size component is 100-1000 μm, the particle size of the fine particle size component is 1-80 μm, and the particle size of the nano particle component is 1-50 nm; Among them, the coarse particle size component is selected from one or more of quartz sand, zinc oxide, and aluminum oxide; the fine particle size component is selected from one or more of aluminum nitride, boron nitride, silicon carbide, graphite, copper powder, and iron powder; the nano component is selected from one or more of nano silver particles, nano copper particles, carbon nano tubes, and graphene; the surfactant is selected from one or more of sodium dodecylbenzene sulfonate, polyvinyl pyrrolidone, and hexadecyltrimethylammonium bromide.
2. The high thermal conductivity cementing admixture according to claim 1, wherein: The cementing admixture comprises: 100 parts by weight of a coarse particle size component, 60-100 parts by weight of a fine particle size component, 0.1-0.5 parts by weight of a nanometer component, and 0.5-2.5 parts by weight of a surfactant.
3. The high thermal conductivity cementing admixture according to claim 2, characterized in that: The cementing admixture comprises: 100 parts by weight of a coarse particle size component, 75-85 parts by weight of a fine particle size component, 0.2-0.3 parts by weight of a nanometer component, and 1-1.5 parts by weight of a surfactant.
4. The high thermal conductivity cementing admixture according to any one of claims 1 to 3, wherein: The coarse-grained components are selected from any two of quartz sand, zinc oxide and aluminum oxide, preferably zinc oxide and aluminum oxide.
5. The high thermal conductivity cementing admixture according to claim 4, wherein: The mass ratio of zinc oxide to aluminum oxide is 1:1-10, preferably 1:3-5.
6. The cementing admixture according to any one of claims 1 to 5, wherein: The fine particle size component is selected from at least two of aluminum nitride, boron nitride, silicon carbide, graphite, copper powder, and iron powder.
7. The cementing admixture according to claim 6, wherein: The fine particle size components are boron nitride, silicon carbide, graphite and copper powder; wherein the mass ratio of the boron nitride, silicon carbide, graphite and copper powder is 1:0.5-1.5:0.2-0.6:1-2.
8. Use of the high thermal conductivity cementing admixture according to claims 1 to 7 in cementing slurry.
9. A cementing slurry, characterized in that: The raw materials for preparing the cementing slurry include: 100 parts by weight of oil well cement, 25-65 parts by weight of the high thermal conductivity cementing admixture described in any one of claims 1-7, 2.5-5 parts by weight of a fluid loss reducer, 1.5-4.5 parts by weight of an early strength agent, 0.25-1 parts by weight of a dispersant, 0.005-0.5 parts by weight of a defoamer and 50-90 parts by weight of water.
10. The cementing slurry according to claim 9, wherein: The oil well cement is selected from Grade G high sulfate resistance oil well cement; Preferably, the fluid loss agent is selected from one or more of DZJ-Y fluid loss agent, carboxymethyl cellulose, polyvinyl alcohol, and hydroxyethyl cellulose; Preferably, the early strength agent is selected from sulfate early strength agents, and is further preferably selected from one or more of sodium sulfate, calcium sulfate, and potassium sulfate; Preferably, the dispersant is selected from polycarboxylic acid dispersants; Preferably, the defoamer is selected from one or more of a polyether defoamer, a silicone defoamer, and an alcohol defoamer.
Citation Information
Patent Citations
Anti-leakage cement paste for well cementation
CN110002798A
High-strength high-toughness high-temperature-resistant oil well cement slurry system as well as preparation method and design method thereof
CN106833567A
Nano-material mixed modified superhigh-temperature high-performance well cementing slurry system and preparation method thereof
CN109679600A
High-thermal-conductivity and high-thermal-insulation cement for geothermal well and preparation method thereof
CN114315256A
